PENGARUH PERMAINAN BAKIAK DAN KECERDASAN INTERPERSONAL TERHADAP PERKEMBANGAN FISIK MOTORIK ANAK TK KHAIRANI ACEH BESAR - Riza Oktariana (Lembaga Penelitian dan Pengabdian (LP2M) STKIP Bina Bangsa Getsempena, 2019)
The development of physical motorism in one of the five aspects of early childhood development, to achieve motoric development especially gross motoric is done through play. Play activities can stimulate children's physical motor development, and become one of the other factors that play an important role in children's psychological improvement, namely interpersonal intelligence. Based on this background, the researchers chose the title